Shower Xmax determination based on LOFAR radio measurements - Buitink, Stijn; Corstanje, Arthur; Emilio Enriquez, J.; Falcke, Heino; Frieswijk, Wilfred; Hörandel, Jörg R.; Krause, Maria; Nelles, Anna; Schellart, Pim; Scholten, Olaf; Thoudam, Satyendra; Veen, Sander T.E.R.; et al. (Proceedings of the 33rd International Cosmic Rays Conference, ICRC 2013, 2013)
LOFAR is a multipurpose radio telescope which can be used for radio detection of cosmic rays while running astronomical observations at the same time. The core of LOFAR contains 2300 antennas within an area of four square kilometer. This high density makes it an ideal location for a detailed study of the radio signal of extensive air showers in the energy range 1016 - 1018 eV. The LORA scintillator array is located at the center of LOFAR and provides a trigger for the system and a reconstruction of the shower parameters. We present an analysis of high quality LOFAR events for which the lateral distribution of the radio signal can be studied in 2D. For each event dedicated simulation sets for proton and iron primaries have been produced. The radio and particle data are fitted simultaneously to the simulation. This leads to a reconstruction of the depth of the shower maximum Xmax, which opens the possibility for cosmic ray composition studies at energies exceeding 1016 eV.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Air showers; Experiments; LOFAR; Radio emission